Negotiations as a non-judicial means of settling international disputes: theoretical and practical issues - Popkov, Andrey N. (Journal of the Belarusian State University. International Relations, 2026)
This article examines the theory and practice of direct negotiations as a non-judicial means of settling disputes concerning the interpretation and application of treaties. It considers the place and function of negotiations in the contemporary system of international dispute settlement, particularly given the growing practice of treating negotiations as a preliminary step before recourse to international judicial bodies. The author analyses in detail the case law of the International Court of Justice and other international courts and tribunals on whether the parties have engaged in good-faith negotiations before seizing an international judicial body. Drawing on international jurisprudence and doctrinal writing, the article highlights the advantages of negotiations, the legal criteria for assessing their quality, and their principal standards and stages. It concludes that direct negotiations remain an important means of settling disputes between states, as well as disputes involving states and foreign natural or legal persons. At the same time, it emphasises the need to avoid a merely formal approach to negotiations when addressing disputes concerning the interpretation and application of treaties before referring to international adjudication.